Local Duck Fanning At Paddy Three Times Planting Areas ("IP Padi 300") - A.R, Setioko; Iskandar, S; Raharjo, Y.C; Soedjana, T.D; Murtisari, T; Purba, M; Estuninngsih, S; Sunandar, N; Sarosa, D (Indonesian Journal of Animal and Veterinary Sciences, 2000)
Most of duck husbandry in Indonesia is still run traditionally, herded in rice field or in the swampy area. This kind of husbandry seemed to be much preferred by farmers as they thought it was a simple and did not need high skill and high capital "IP padi 300" was a term of rice planting system tree times instead of twice in a year. This kind of changing might have significantly affected duck faming. The objective of the study was to observe the interactively effect of "IP padi 300" to duck husbandry at the same area. Two locations were choosen (Subang, West Jawa and Pemalang, Central Java) with 5 farmers at each location to be involved in the study. As many as 1200 laying pullet ducks were distributed to 10 farmers at two locations. The farmers were suggested to raise laying ducks with their own systems (fully intensive, semi intensive and fully herded) and were observed for 6 months. Biota was observed on both field and in the crop of the laying ducks. There was an interactive effect of "IP padi 300" and the duck farming on the same area. The availability of feed was increased on the "IP padi 300", which gave benefit to duck farming especially fue herded system, not to go far from owners home base. Whilst the benefit to "IP padi 300" was assumed to the reduction of pest and desease, which was frequently attacked the rice field. The production of egg from herded duck was very fluctuative due to the movement and feed availability in the rice field. Field biota in Subang and Pemalang was very much the same in profile, although "golden snail" was only found in Subang. Ducks crop content seemed to be very much similar with the profile of field biota, although rice grain was the most in the crop. Thus, it was found that field biota was not reduced by "IP padi 300", in fact it was rather increased. Â  Key words: IP 300, herded ducks, duck farming